Does green finance and energy policy paradox demonstrate green economic recovery: Role of social capital and public health - Xu, Li; Xu, Chao (Frontiers in Public Health, 2022)
Green economy development has become a mainstream value orientation in social and global economic development to protect and improve the ecological environment. Multiple stakeholders are needed to address complex issues like climate change and its impact on the ecological environment and public health. This study investigates the impact of energy policy and green finance on green economic recovery via the controlling role of social capital and public health. An entropy approach was used to measure the green economic index in addition to an econometric approximation for interpreting the longitudinal dataset for the scenarios for E7 countries between 2010 and 2020. The findings show that the development of green finance significantly improves green productivity. Higher levels of economic and social conditions, a lower level of public involvement in environmental protection, and a higher level of pollution amplify this positive effect. On the other hand, energy policy can enhance the impact of green finance development. The findings suggest that the empirical findings benefit green finance planning and energy policy.